PENERAPAN PEWARNAAN GRAF UNTUK MENINGKATKAN EFISIENSI PENJADWALAN MENGAJAR GURU DI MTS AL-KHOIRIYAH - Hamid, Nur; Maghfirah, Hidayatul; Su'aibah, Siti; Jawad, Muhammad; Khoiruman, Muhammad; Hafiizh, Mochammad (UNIVERSITAS NEGERI MALANG, 2023)
Scheduling subjects in a school often gives a conflicting schedule to some teachers. On the other hand, graph theory can help to solve. One of the methods to solve the problem is implementing a coloring graph. In this paper, we apply the coloring graph using the Welch-Powell algorithm for scheduling subjects in MTs Al-Khoiriyah.Keywords: Welch-Powell algorithm, Coloring graph.